2020
DOI: 10.1161/jaha.120.015359
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Systolic Blood Pressure Variability and Kidney Disease Progression in Patients With Chronic Kidney Disease: Results From C‐STRIDE

Abstract: Background It is unclear whether short‐term blood pressure variability is associated with renal outcomes in patients with chronic kidney disease. Methods and Results This study analyzed data from participants in the C‐ STRIDE (Chinese Cohort Study of Chronic Kidney Disease) who had chronic kidney disease stages 1 to 4. Short‐term blood pressure variability was measured by calculating the we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…20 Wang and colleagues reported that wSD was associated with the risk of dialysis initiation and/or transplantation in patients with CKD. 21 However, in the telehealth-based Vascular health Assessment of the hypertensive (VASOTENS) Registry, 24-h SBP ARV was not associated with neither decreased eGFR nor increased urine albumin excretion in hypertensive patients. 22 Due to conflicting data, more evidence is still needed to comprehensively investigate the impact of mean BP and various BPV parameters on renal function decline in hypertensive patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…20 Wang and colleagues reported that wSD was associated with the risk of dialysis initiation and/or transplantation in patients with CKD. 21 However, in the telehealth-based Vascular health Assessment of the hypertensive (VASOTENS) Registry, 24-h SBP ARV was not associated with neither decreased eGFR nor increased urine albumin excretion in hypertensive patients. 22 Due to conflicting data, more evidence is still needed to comprehensively investigate the impact of mean BP and various BPV parameters on renal function decline in hypertensive patients.…”
Section: Discussionmentioning
confidence: 98%
“…20 Wang and colleagues reported that wSD was associated with the risk of dialysis initiation and/or transplantation in patients with CKD. 21 To the best of our knowledge, the current study first conducted a prospective evaluation of the relationship between five different short-term BPV parameters derived from ABPM and hypertensive nephropathy in Han Chinese hypertensive patients. The current study showed that 24-h mean BP was more important than shortterm BPV in the prevention of hypertensive nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…C-STRIDE is an ongoing cohort study initiated in November 2011, which includes patients with stage 1–4 CKD and various etiologies in 39 tertiary academic hospitals around China. The detailed study design and methods have been published previously [10, 11]. There are 2 criteria to be eligible for enrollment.…”
Section: Methodsmentioning
confidence: 99%
“…Tubular injury do to hypertension is associated to damage of peritubular capillaries which triggers hypoxia, microvasculature dysfunction, inflammation and finally turns into intersitial fibrosis [37]. Together with chronic uncontrolled hypertension, BP variability is also associated to a high risk of renal outcomes [38,39]. Observations from our cohort of CKD patients linked BP variability with a prevalence of sleep disorders such as obstructive sleep apnea, insomnia and restless leg syndrome further supporting the hypothesis that endothelial dysfunction and glomerular damage play a crucial role in the development of BP variation and in worsen disease progression in these patients [40][41][42].…”
Section: Oxidative Stress Damage In Ckd and Kidney Failure With Or Without Replacement Therapy Patientsmentioning
confidence: 99%